Sanat, Texnh : Fourteen Turkish and Greek Contemporary Artists. (Istanbul : MSU Istanbul Painting and Sculpture Museum, 1992)
Alithinos, Dimitri ; Beykal, Canan ; Birsel, Selim ; Arkmen, Ayse ; Kirza, Serhat ; Liodaki, Niki ; Onur, Füsun ; Osman ; Papaphilippou, Aimilia ; Saray, Ismail ; Sfikas, George ; Spiliopoulos, Marios ; Theodoros
Sanat, Texnh : Fourteen Turkish and Greek Contemporary Artists, MSU Istanbul Painting and Sculpture Museum, Istanbul, 25th March - 18th April 1992
boek
Keywords: Griekenland; Turkije